Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model. (1st May 2023) - Chen, Shan; Yang, Jin-Lei; Zhang, Yao-Sheng; Wang, Hong-Yu; Lin, Xin-Ying; Xue, Rong-Yue; Li, Meng-Ya; Li, Shi-Wei; Juhasz, Albert L.; Ma, Lena Q.; Zhou, Dong-Mei; Li, Hong-Bo
Abstract: Microplastics exposure is a new human health crisis. Although progress in understanding health effects of microplastic exposure has been made, microplastic impacts on absorption of co-exposure toxic pollutants such as arsenic (As), i.e., oral bioavailability, remain unclear. Microplastic ingestion may interfere As biotransformation, gut microbiota, and/or gut metabolites, thereby affecting As oral bioavailability. Here, mice were exposed to arsenate (6 μg As g −1 ) alone and in combination with polyethylene particles of 30 and 200 μm (PE-30 and PE-200 having surface area of 2.17 × 10 3 and 3.23 × 10 2  cm 2  g −1 ) in diet (2, 20, and 200 μg PE g −1 ) to determine the influence of microplastic co-ingestion on arsenic (As) oral bioavailability. By determining the percentage of cumulative As consumption recovered in urine of mice, As oral bioavailability increased significantly ( P  < 0.05) from 72.0 ± 5.41% to 89.7 ± 6.33% with PE-30 at 200 μg PE g −1 rather than with PE-200 at 2, 20, and 200 μg PE g −1 (58.5 ± 19.0%, 72.3 ± 6.28%, and 69.2 ± 17.8%). Both PE-30 and PE-200 exerted limited effects on pre- and post-absorption As biotransformation in intestinal content, intestine tissue, feces, and urine. They affected gut microbiota dose-dependently, with lower exposure concentrations having more pronounced effects. Consistent with the PE-30-specific As oral bioavailability increase, PE exposure significantly up-regulated gut metabolite expression, and PE-30 exerted greater effects than PE-200, suggesting that gut metabolite changes may contribute to As oral bioavailability increase. This was supported by 1.58–4.07-fold higher As solubility in the presence of up-regulated metabolites (e.g., amino acid derivatives, organic acids, and pyrimidines and purines) in the intestinal tract assessed by an in vitro assay. Our results suggested that microplastic exposure especially smaller particles may exacerbate the oral bioavailability of As, providing a new angle to understand health effects of microplastics. Graphical abstract: Image 1 Highlights: PE-30 not PE-200 ingestion significantly increased As oral bioavailability in mice. Both PE-30 and PE-200 ingestion affected gut microbiota dose-dependently. Arsenic biotransformation was not affected by both PE-30 and PE-200 ingestion. PE-30 ingestion was more effective in leading to gut metabolite expression up-regulation.